Impact of Alternative Diets on Athletes: Analyzing Influence on Athletic Performance - Jolanta Mędyk; Michał Rogulski; Yauheniya Patarocha; Aleksandra Ślusarska; Paulina Błasiak; Małgorzata Wirkijowska; Patryk Mikołajec; Ruslan Huk; Barbara Bilecka; Jakub Wirkijowski (Journal of Education, Health and Sport)
Diet plays a significant role in athletes' lives due to its impact on both their performance and health. Gaining a deeper insight into how diet affects athletic outcomes is crucial for designing nutritional strategies that meet the unique demands and goals of each athlete. While a variety of studies have examined different aspects of sports nutrition, there is still a clear need for further investigation in this field. This review examines the effects of alternative dietary approaches, including plant-based diets, ketogenic diets, and intermittent fasting, on athletic health and performance. Drawing on research published from 2014 to 2024, the focus is placed on experimental and systematic studies. The findings suggest that well-planned plant-based diets can deliver notable health benefits, lower the risk of chronic illnesses, and enhance aerobic capacity without hindering performance. In contrast, ketogenic diets, while potentially effective for weight loss, present concerns related to cardiovascular and bone health and may impair performance in high-intensity activities. Intermittent fasting, though showing little impact on resistance training, might negatively affect endurance performance. Overall, plant-based diets stand out as offering the most favorable combination of health advantages and performance support. To enable athletes to make well-informed dietary choices that align with their specific needs, further studies with improved methodologies are essential.